2010
DOI: 10.1352/1944-7558-115.4.277
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons Between Individuals With Autism Spectrum Disorders and Individuals With Down Syndrome in Adulthood

Abstract: Differences between 70 adults with autism spectrum disorders (ASD) and intellectual disability and 70 age-matched adults with Down syndrome (DS) were examined on variables indicative of independence in adult life. Adults with ASD had less residential independence and social contact with friends, had more limited functional abilities and literacy, exhibited more behavior problems, had more unmet service needs, and received fewer services as compared to adults with DS. Reflecting these differences, adults with A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
62
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(70 citation statements)
references
References 32 publications
7
62
1
Order By: Relevance
“…Examination of the specific diagnoses of the adults who continued to live at home versus those who did not live with their parents at this stage of life revealed that adults with DS were considerably more likely to live at home than adults with ASD, cerebral palsy, or other IDD conditions. Past research has also shown higher rates of co-residence in adults with DS than adults with ASD (e.g., Esbensen, Bishop, Seltzer, Greenberg, & Taylor, 2010), and our findings are consistent in this respect.…”
Section: Discussionsupporting
confidence: 90%
“…Examination of the specific diagnoses of the adults who continued to live at home versus those who did not live with their parents at this stage of life revealed that adults with DS were considerably more likely to live at home than adults with ASD, cerebral palsy, or other IDD conditions. Past research has also shown higher rates of co-residence in adults with DS than adults with ASD (e.g., Esbensen, Bishop, Seltzer, Greenberg, & Taylor, 2010), and our findings are consistent in this respect.…”
Section: Discussionsupporting
confidence: 90%
“…Mothers of children with Down syndrome report a lower level of parenting stress and view caretaking more positively than mothers of children with other types of DD (Hodapp, Ly, Fidler, & Ricci, 2001; Hodapp, Ricci, Ly, & Fidler, 2003; Sellinger & Hodapp, 2005). This “Down syndrome advantage” continues during mothers’ midlife, when their son or daughter is an adolescent or adult (e.g., Abbeduto et al, 2004; Esbensen, Bishop, Seltzer, Greenberg, & Taylor, 2010) and is also evident in fathers (Hartley et al, in press). The “Down syndrome advantage” is purported to be related to a variety of factors including the certainty (i.e., genetic testing) and early timing of diagnosis, profile of less negative and more positive behaviors displayed by individuals with Down syndrome compared to children with other DDs, and possibly parent resources (e.g., older and more educated mothers), although recent evidence suggests that maternal age and education do not contribute to this advantage (Esbensen & Seltzer, 2011).…”
Section: Why Some Marriages Fare Better Than Othersmentioning
confidence: 99%
“…One study of 19 individuals of age 21-26 found that 73.7% had never had paid employment (Howlin, Mawhood, & Rutter, 2000). In Taylor and Seltzer's 2011 study, 6.1% of participants of age 19-25 had competitive employment, whereas 12.1% and 56.1% were engaged in supported employment and sheltered employment, respectively, findings mirrored by a survey of 70 adults with an average age of 37 (Esbensen, Bishop, Seltzer, Greenberg, & Taylor, 2010;Taylor & Seltzer, 2011). A larger study (n ÂŒ 500) found that 55.1% of the sample had had paid employment at some time within the first 6 years after exiting high school (Shattuck et al, 2012), but putting their employment rate in perspective, another study found that young adults with ASDs were the second least likely to have held paid employment compared with adults with other types of disabilities (Eaves & Ho, 2008;Newman et al, 2011).…”
mentioning
confidence: 93%